Stakeholder Perspectives on the Meaningful Integration of Clinical Informatics Interventions Using Patient-Reported Outcomes in Healthcare - Russell, David; Sharma, Yashika; Ambrosy, Andrew P.; Axsom, Kelly; Chaiyasit, Janejira J.; Cuomo, Margaret O.; Deaton, Christi; Goldberg, Anne J.; Goyal, Parag; Guan, Angel; Polubriaginof, Fernanda C. G.; McGurk, Lucy; Sandhu, Alexander T.; Spertus, John A.; Turchioe, Meghan Reading; Vawdrey, David K.; Creber, Ruth Masterson (ACI Open, 2024)
Background Patient-reported outcomes (PROs) capture where patients are on their disease trajectory and can identify changes in health status from their perspective.Objectives This study applied the equity and sustainability-informed RE-AIM framework (Reach, Effectiveness, Adoption, Implementation, and Maintenance) to gain insights into clinical informatics interventions for collection and use of PROs across health systems.Methods A total of 14 health informatics and clinical professionals were interviewed about the development and use of PROs within their health systems and individual practices. Directed content analysis was performed to highlight patterns, similarities, and differences in stakeholder perspectives across RE-AIM domains.Results The reach of clinical informatics interventions using PROs varied across clinical practices and settings based upon institutional commitment and support, integration of clinical information systems, and engagement with patients and families. Although interventions using PROs were viewed as effective for enabling focused conversations with patients and facilitating shared decision-making, barriers to adoption included licensing requirements associated with PRO instruments, lack of incentives for their use, limited integration of PRO results into electronic medical record systems, and poor support for patients with low technology and/or health literacy. Implementation of interventions using PROs was facilitated through training and support staff who aided clinicians with clinical workflow integration, availability of questionnaires in multiple languages, identifying thresholds and strategies for action, and presenting interpretable visualizations showing changes over time alongside significant clinical events. Maintenance of interventions using PROs was enabled through multimodal data collection approaches and data governance groups that evaluated organizational requests to track new measures.Conclusion Initiatives to increase the reach of clinical informatics interventions using PROs will require health system investments into medical record system integration, education, and implementation support for clinicians and patients, and efforts to reach patient populations with language barriers or limited technology literacy.
Keywords: patient-reported outcomes; qualitative; RE-AIM; equity; sustainability